The micro-macro dilemma in sociology: Perplexities and perspectives - Tsekeris Charalambos; Lydaki Anna (Sociologija, 2011)
The micro-macro or agency-structure question is indisputably one of the most important theoretical issues within the human and social sciences. The main purpose of this paper is to carefully explore, fruitfully overview and comprehensively critique the contemporary sociological literature on micro (agency) and macro (structure), from a reflexive-dialectical standpoint. This particular standpoint strategically emphasizes both the circularity and the relative autonomy of structures vis à vis actors, or of institutions vis à vis individuals. In this analytic context, it is critically discussed the varied notion of a middle position on the ongoing theoretical debate between positivism and constructivism, as well as the epistemologically beneficial role that meta-theoretical reflexivity and the internal conversation can potentially play in this debate. In specific, the internal conversation (Margaret Archer) gives a reflexive-dialectical impetus to the micro-macro relationship, while embracing a needed analytical dualism (not necessarily an ontological one).